2008
DOI: 10.1214/08-aoas176
|View full text |Cite
|
Sign up to set email alerts
|

Estimating a difference of Kullback–Leibler risks using a normalized difference of AIC

Abstract: Estimating a difference between Kullback-Leibler risks by a normalized difference of AIC SUMMARY AIC is commonly used for model selection but the precise value of AIC has no direct interpretation. We are interested in quantifying a difference of risks between two models. This may be useful for both an explanatory point of view or for prediction, where a simpler model may be preferred if it does nearly as well as a more complex model. The difference of risks can be interpreted by linking the risks with relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…A simple formula allows to estimate these variances and to construct so-called tracking intervals; our simulation study however shows that the coverage of these tracking intervals is too large, due to an overestimation of the variances. This is an open question to find why this happened here while in other contexts [15,19] the coverage rates were correct, and possibly to find a correction to this overestimation; nevertheless, the estimates get the correct order of magnitude and the tracking intervals may be useful.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…A simple formula allows to estimate these variances and to construct so-called tracking intervals; our simulation study however shows that the coverage of these tracking intervals is too large, due to an overestimation of the variances. This is an open question to find why this happened here while in other contexts [15,19] the coverage rates were correct, and possibly to find a correction to this overestimation; nevertheless, the estimates get the correct order of magnitude and the tracking intervals may be useful.…”
Section: Resultsmentioning
confidence: 92%
“…However, in the conventional theory of point and interval estimation, the target parameter is fixed; here, it changes with n. Thus, we have a moving target: hence the name of tracking interval. Some simulations in Commenges et al [19] showed that the variance of the difference of AIC was correctly estimated and the corresponding tracking interval had good coverage properties. The same idea can be applied in the more general case treated here.…”
Section: Asymptotic Distribution Of a Difference Between Uacvr Valuesmentioning
confidence: 98%
See 3 more Smart Citations